George Hamandishe Karekwaivanane, The Struggle over State Power in Zimbabwe: Law and Politics since 1950 (Historia, 2021)
The struggle over state power throughout Zimbabwe’s modern history has been a complex affair. Literature has demonstrated that the contestations had several interesting dimensions, involving such issues as land, labour, religion and ethnicity. However, what remains understudied is the position of law in the struggle. Yet, the law was central in the constitution of both the colonial and the post-colonial Zimbabwean state. Against this background, George Karekwaivanane’s The struggle over state power in Zimbabwe, which grapples with the interplay between law and politics between 1950 and 2008, is a welcome contribution to Zimbabwe’s social and legal historiography. This strand of Zimbabwe’s social and political history takes forward key debates about how scholars have sought to understand the relationship between law and state power. By nuancing the role of law in struggles over state power, the book offers a useful window into the continuous process of making and remaking the state.
Keywords: Zimbabwe; George Hamandishe Karekwaivanane; labour; 2008; state